THE HIERARCHICAL RELATIONSHIP BETWEEN BRAND EQUITY DIMENSIONS - Hayan Dib; Abdullah Alhaddad (European Scientific Journal, ESJ, 2014)
Brands have been considered as the second most important assets for a firm after customers .This study proposes a brand equity model with four dimensions: brand awareness, brand trust, perceived quality, and brand loyalty. In addition, the relationships among four dimensions and their effects on brand equity are investigated empirically. In order to accomplish the objectives proposed, a model reflecting the hierarchical relationship between the brand equity dimensions of brand awareness, brand trust, perceived quality and brand loyalty and brand equity, the model is tested by structural equations and the sample is 369 students from the higher institute of business administration (HIBA), the finding show that perceived quality does not has a significant influence on both brand trust and brand equity, on other hand, the rest of relationship between brand equity dimensions and brand equity is confirmed . The study finding can be used by mobile market in creating brand equity by using some strategies which can lead to the brand equity.